Soft soil solidifying agent and preparation method and use method thereof
By using expanded fly ash in soft soil curing agent and combining high-water absorption resin treatment technology, the environmental impact and construction efficiency problems of traditional soft soil curing agents when treating ultra-soft soil and special soil are solved, and efficient soft soil curing effect is achieved, with the advantages of energy saving and environmental protection.
Patent Information
- Application Number
- CN202411658912.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-20
AI Technical Summary
When dealing with super soft soil and special soil, existing soft soil curing agents have problems such as large discharge volume of engineering waste soil, large environmental impact, slow construction speed, and waste of resources. Traditional methods require a large amount of sand and gravel materials, which affects energy conservation and environmental protection.
Using soft soil curing agents including lime, slag, cement and expanded fly ash, the expanded fly ash is prepared by treating high-water absorption resin. It can absorb a large amount of water and expand in the early stage of hydration, increase the early stage strength, and gradually release moisture in the later stage to increase the strength in the later stage of curing.
It effectively improves the early and later strength of soft soil curing agent, reduces dependence on sand and gravel materials, reduces the discharge volume of project waste soil, improves construction speed and resource utilization efficiency, and has the advantages of energy saving and environmental protection.
Smart Images

Figure CN119143462B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of soft soil curing agents, and in particular to a soft soil curing agent and a preparation method and a use method thereof. Background Art
[0002] With the development of engineering construction, we are encountering more and more super-soft soil and special soil complex foundations, such as: land reclamation foundation, river ponds, fish ponds, swamp foundations, mud dumps, contaminated soil, etc. If the traditional method is used for replacement, a large amount of engineering waste soil will be generated, and a large amount of high-quality fillers such as sand and gravel will be required. The transportation, stacking and abandonment of waste soil will also affect urban sanitation and traffic. In addition, in the process of road soft foundation treatment, we often encounter some sections without hard crust layers, where the strength and bearing capacity of the surface soil are extremely low, making it impossible for equipment to enter.
[0003] The existing soft soil strata are mostly solidified through replacement and filling methods. The amount of engineering waste soil discharged is large, and the transportation and abandonment have an impact on the environment. A large amount of replacement materials are needed, the amount of sand and gravel increases, and mountain quarrying and river sand excavation are required, which have an impact on surrounding buildings. In addition, the construction speed is slow, resulting in a waste of resources and is not energy-saving and environmentally friendly. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a soft soil solidifying agent which can effectively improve the solidification strength.
[0005] Another technical problem to be solved by the present invention is to provide a method for preparing a soft soil solidifying agent.
[0006] Another technical problem to be solved by the present invention is to provide a method for using the soft soil solidifying agent.
[0007] In order to solve the above technical problems, the present invention provides a soft soil solidifying agent, which comprises the following components in parts by weight:
[0008] 10~20 parts of lime, 20~50 parts of slag, 20~30 parts of cement, 20~30 parts of expanded fly ash;
[0009] The expanded fly ash is obtained by grafting a highly absorbent resin onto the surface of fly ash.
[0010] As an improvement of the above technical solution, the preparation method of expanded fly ash comprises the following steps:
[0011] (1) Sorting the fly ash to remove floating beads and carbon particles in the fly ash to obtain a first intermediate;
[0012] (2) treating the first intermediate with an alkali solution having a concentration of 10 g / L to 30 g / L for 0.2 h to 0.5 h to obtain a second intermediate;
[0013] (3) uniformly mixing acrylic acid, acrylamide, glycerol triglycidyl ether and water in a weight ratio of (1-2):(0.5-1.5):(0.001-0.005):(2-5), adding the second intermediate, and mixing thoroughly to obtain a third intermediate; wherein the weight ratio of the second intermediate to acrylic acid is (5-15):1, and the degree of neutralization of the acrylic acid is 60%-80%;
[0014] (4) adding an initiator to the third intermediate and reacting at 60° C. to 90° C. for 10 h to 20 h to obtain a fourth intermediate;
[0015] (5) Drying the fourth intermediate and crushing it to a size below 100 meshes to obtain expanded fly ash.
[0016] As an improvement of the above technical solution, step (1) includes:
[0017] (1.1) Mix fly ash and water to obtain a first slurry with a concentration of 20wt% to 40wt%, and remove the floating beads on the surface after standing;
[0018] (1.2) Using diesel as a collector and octanol as a frother, the first pulp is floated, and the first pulp after flotation is filtered and dried to obtain a first intermediate;
[0019] The weight ratio of the diesel to the fly ash is (0.3-1.5):1000, the weight ratio of the octanol to the fly ash is (0.4-1.5):1000, the flotation time is 3-5 min, and the aeration volume is 0.1 m 3 / (m 2 ·min)~0.5m 3 / (m 2 ·min).
[0020] As an improvement of the above technical solution, in step (2), the alkali solution is a NaOH aqueous solution or a KOH aqueous solution, and its temperature is 50°C to 80°C;
[0021] The ratio of the alkali solution to the first intermediate is 100 mL: (20-30) g.
[0022] As an improvement of the above technical solution, the initiator is selected from one or more of azobisisobutylimidazoline hydrochloride, 1-hydroxycyclohexylphenyl ketone, ammonium persulfate, and potassium persulfate.
[0023] As an improvement of the above technical solution, in step (2), the alkali solution is a NaOH aqueous solution, and the temperature thereof is 50° C. to 70° C.; and / or
[0024] In step (3), acrylic acid, acrylamide, propylene glycol triglycidyl ether and water are uniformly mixed in a weight ratio of (1.5-2): (0.5-1): (0.001-0.003): (4-5), and the second intermediate is added and mixed thoroughly to obtain a third intermediate; wherein the weight ratio of the second intermediate to acrylic acid is (10-15): 1, and the degree of neutralization of the acrylic acid is 60%-70%; and / or
[0025] In step (4), the initiator is 1-hydroxycyclohexyl phenyl ketone, the reaction temperature is 70° C. to 80° C., and the reaction time is 10 h to 15 h.
[0026] As an improvement of the above technical solution, it also includes 2 to 5 parts of a conditioning agent;
[0027] The conditioning agent is polyacrylamide and / or chitosan.
[0028] As an improvement of the above technical solution, the slag is S95 grade slag powder or S105 grade slag powder; and / or
[0029] The cement is PO42.5 grade cement or PO52.5 grade cement.
[0030] Correspondingly, the present invention also discloses a method for preparing a soft soil curing agent, which is used to prepare the soft soil curing agent, and comprises:
[0031] Mixing lime, slag and cement uniformly to obtain a mixture;
[0032] Providing / preparing expanded fly ash;
[0033] The mixture and the expanded fly ash are packaged separately to obtain the product.
[0034] Correspondingly, the present invention also discloses a method for using a soft soil solidifying agent, which is used to use the soft soil solidifying agent, and comprises:
[0035] Mixing expanded fly ash with the shallow surface soft soil to be solidified;
[0036] The mixture obtained by mixing lime, slag and cement is added into the shallow surface soft soil to be solidified which has been mixed with expanded fly ash, and mixed.
[0037] The implementation of the present invention has the following beneficial effects:
[0038] The soft soil solidifying agent of the present invention comprises the following components by weight: 10 to 20 parts of lime, 20 to 50 parts of slag, 20 to 30 parts of cement, and 20 to 30 parts of expanded fly ash; wherein the expanded fly ash is obtained by grafting a highly absorbent resin on the surface of fly ash. The expanded fly ash in the present invention can absorb a large amount of water to expand in the early stage of hydration, thereby improving the early strength, and can gradually release water in the later stage, thereby improving the strength in the later stage of solidification. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is an electron microscope image of fly ash before treatment in one embodiment of the present invention;
[0040] Figure 2 This is an electron microscope image of the second intermediate after step S12 in one embodiment of the present invention;
[0041] Figure 3 is an electron microscope image of the second intermediate after step S12 in another embodiment of the present invention;
[0042] Figure 4 This is an electron microscope image of expanded fly ash in one embodiment of the present invention. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0044] The present invention provides a soft soil solidifying agent, which comprises the following components in parts by weight:
[0045] 10~20 parts of lime, 20~50 parts of slag, 20~30 parts of cement, 20~30 parts of expanded fly ash;
[0046] Among them, the expanded fly ash is obtained by grafting a highly absorbent resin on the surface of fly ash. The highly absorbent resin can be one or more of polyacrylate, polyacrylic acid-acrylamide, polymaleic acid-acrylamide, cellulose, and polyacrylamide, but is not limited thereto. The expanded fly ash in the present invention can absorb a large amount of water and expand in the early stage of solidification, fill the gaps in the soft soil, and improve the solidification effect; moreover, a large amount of water absorption can prevent the generation of a large amount of hydrated calcium silicate gel in the early stage of hydration, thereby increasing the content of calcium sulfonate and improving the early strength of the solidified sample. Furthermore, the expanded fly ash after absorbing water will gradually release water in the later hydration process, further promoting the hydration reaction, forming a large amount of reinforcing phases such as calcium sulfonate and calcium sulfate, and effectively improving the later strength of the solidified sample.
[0047] Specifically, fly ash can be directly mixed with the monomer used for the super absorbent resin, and then a cross-linking agent and an initiator are added to react, and after the reaction, the fly ash is crushed to a desired particle size to obtain expanded fly ash, but the invention is not limited thereto. Exemplarily, in one embodiment, the method for preparing expanded fly ash includes the following steps:
[0048] S1: Mix acrylic acid, acrylamide, propylene glycol triglycidyl ether and water evenly, add fly ash and mix thoroughly;
[0049] S2: Add initiator and react to obtain intermediate;
[0050] S3: drying the intermediate and crushing it to less than 100 meshes to obtain expanded fly ash.
[0051] Specifically, in step S1, the neutralization degree of acrylic acid monomer is 60% to 80%. The weight ratio of acrylic acid, acrylamide, propylene glycol triglycidyl ether, and water is (1 to 2): (0.5 to 1.5): (0.001 to 0.005): (2 to 5). The weight ratio of fly ash to acrylic acid is (5 to 12): 1.
[0052] Specifically, in step S2, the initiator can be selected from one or more of azobisisobutylimidazoline hydrochloride, 1-hydroxycyclohexylphenyl ketone, ammonium persulfate, and potassium persulfate, but is not limited thereto. The amount of the initiator used is 0.01wt% to 0.05wt% of the acrylic acid.
[0053] Specifically, in step S2, the reaction temperature is 60°C to 90°C, and the reaction time is 10h to 20h.
[0054] Preferably, in one embodiment of the present invention, the method for preparing expanded fly ash comprises the following steps:
[0055] S11: sorting the fly ash to remove floating beads and carbon particles in the fly ash to obtain a first intermediate;
[0056] S12: treating the first intermediate with an alkali solution to obtain a second intermediate;
[0057] S13: mixing acrylic acid, acrylamide, propylene glycol triglycidyl ether and water uniformly, adding the second intermediate, and mixing thoroughly to obtain a third intermediate;
[0058] S14: adding an initiator to the third intermediate to react to obtain a fourth intermediate;
[0059] S15: drying the fourth intermediate and crushing it to less than 100 meshes to obtain expanded fly ash.
[0060] Specifically, since fly ash is solid waste collected in flue gas after coal combustion, its mineral composition is complex, including unburned carbon particles, glass generated at high temperature (a mixture of three or more of silicon, aluminum, calcium, magnesium, sodium, potassium, iron and titanium), and some crystalline phases (such as mullite, corundum, calcium sulfate, iron oxide, titanium oxide), etc. In the process of coal combustion, the high temperature generated by the combustion causes some minerals in the coal to melt and react to form glass, which cools down rapidly after being discharged from the flue. The glass generated at high temperature will shrink when the temperature drops suddenly to form some hollow microspheres (commonly known as floating beads); the glass will also wrap some crystalline phases to obtain solid or semi-solid microspheres; in addition, some residual carbon particles will adhere to the surface of the microspheres (see Figure 1 , the irregular shaped particles on the surface of the microbeads are carbon particles). When using fly ash, traditional soft soil curing agents generally use hollow floating beads or fly ash as a whole. This is because the hollow floating beads are mainly highly active glass, which can quickly combine with other components (such as cement, slag, etc.) to form calcium silicate hydrate (CSH), thereby improving the curing strength. However, the inventors found in the experimental process for high-water content soft soil that if a large amount of calcium silicate hydrate (CSH) is formed in the early stage of hydration, it will form CSH gel in the high-water content system, which will cause the content of calcium sulfonate, the main curing phase, to be relatively low, resulting in low initial strength. On the other hand, the carbon particles on the surface of the fly ash microbeads will also cause uneven mixing of the monomer and fly ash when grafting the super absorbent resin. To this end, the present invention first removes the floating beads and carbon particles in the fly ash by sorting, and then removes the glass wrapped on the surface of the solid or semi-solid microbeads by a weak base (see Figure 2 , Figure 3 ), and then grafted super absorbent resin particles on the surface of the crystals in the exposed fly ash microspheres to form expanded fly ash (ref. Figure 4 ). When the expanded fly ash obtained by the above-mentioned preparation method is just added to the soft soil to be solidified, the highly absorbent resin particles attached to the surface of the expanded fly ash will absorb water and swell, filling the pores of the soft soil. At the same time, the crystal phase (such as mullite, corundum, etc.) exposed by the original glass microbeads in the expanded fly ash will provide strength, greatly improving the early curing strength; moreover, the expanded fly ash also avoids the formation of excessive CSH gel in the early stage. In the later stage of hydration, the highly absorbent resin particles will also release water under the alkaline conditions formed by hydration, further promoting hydration, increasing the amount of calcium aluminate generated, and effectively improving the strength in the later stage of curing. That is, the expanded fly ash prepared based on the above-mentioned preparation method not only effectively improves the early strength of the soft soil curing agent, but also improves the strength in the later stage of curing.
[0061] Specifically, the fly ash in the present invention is fly ash produced by burning anthracite or bituminous coal, which has a low CaO content, a low glass content, a large number of applicable components, and a small carbon particle content, and is easy to handle. Specifically, the total content of SiO2 and Al2O3 in the fly ash is greater than or equal to 65wt%, and the CaO content is ≤6wt%. More specifically, the total content of SiO2 and Al2O3 in the fly ash is 68wt%~80wt%, and the CaO content is 1wt%~5wt%.
[0062] Specifically, in step S11, the floating beads and carbon particles in the fly ash can be separated by flotation, cyclone dust collector air separation, etc., but it is not limited thereto. Preferably, in one embodiment, step S11 includes the following steps:
[0063] S111: mixing fly ash with water to obtain a first slurry with a concentration of 20wt% to 40wt%, and removing floating beads on the surface after standing;
[0064] S112: flotation of the first slurry using diesel as a collector and octanol as a frother, filtering and drying the first slurry after flotation to obtain a first intermediate;
[0065] The weight ratio of diesel to fly ash is (0.3-1.5):1000, the weight ratio of octanol to fly ash is (0.4-1.5):1000, the flotation time is 3-5 min, and the aeration volume is 0.1 m 3 / (m 2 ·min)~0.5m 3 / (m 2 ·min).
[0066] Specifically, in step S12, the alkali solution is a NaOH aqueous solution or a KOH aqueous solution, but is not limited thereto. Preferably, it is a NaOH aqueous solution. The concentration of the alkali solution is 10 g / L to 30 g / L, and the temperature is 50°C to 80°C. If the concentration is too high or the temperature is too high, it will react with the silicon-rich glass on the surface of the microbeads to form sodium silicate or hydrated sodium silicate, and re-encapsulate the crystals; if the concentration of the alkali solution is too low, the glass cannot be effectively removed. The alkali solution treatment time is 0.5h to 0.8h.
[0067] Specifically, in step S13, the neutralization degree of the acrylic acid monomer is 60% to 80%. The reaction speed of the acrylic acid monomer with this neutralization degree is suitable, and the water absorption rate of the resin obtained by polymerization is high. Preferably, the neutralization degree of the acrylic acid monomer is 60% to 70%.
[0068] Specifically, in step S13, the weight ratio of acrylic acid, acrylamide, glycerol triglycidyl ether, and water with a neutralization degree of 60% to 80% is (1 to 2): (0.5 to 1.5): (0.001 to 0.005): (2 to 5). The present invention uses acrylic acid and acrylamide as polymerization monomers and glycerol triglycidyl ether as a cross-linking monomer for copolymerization. The highly absorbent resin particles prepared can be well attached to the surface of fly ash particles after alkali etching, and play a role in water absorption and swelling. Preferably, the weight ratio of acrylic acid, acrylamide, glycerol triglycidyl ether, and water with a neutralization degree of 60% to 80% is (1.5 to 2): (0.5 to 1): (0.001 to 0.003): (4 to 5).
[0069] Specifically, in step S13, the weight ratio of the second intermediate to acrylic acid is (5-15):1. If the amount of the second intermediate is too small, it is easy to cause the expanded fly ash to absorb too much water in the early stage, the hydration degree is reduced, and the early curing strength is small. If the amount of the second intermediate is too large, the expanded fly ash absorbs less water and the early curing strength is relatively small. Preferably, the weight ratio of the second intermediate to acrylic acid is (10-15):1.
[0070] Specifically, in step S14, the initiator can be selected from one or more of azobisisobutylimidazoline hydrochloride, 1-hydroxycyclohexylphenyl ketone, ammonium persulfate, and potassium persulfate, but is not limited thereto. Preferably, in one embodiment, the initiator is 1-hydroxycyclohexylphenyl ketone. Specifically, the amount of the initiator is 0.01wt% to 0.05wt% of the acrylic acid.
[0071] Specifically, in step S14, the reaction temperature is 60°C to 90°C, and the reaction time is 10h to 20h. Preferably, the reaction temperature is 70°C to 80°C, and the reaction time is 10h to 15h.
[0072] Specifically, in the formula of the soft soil solidifying agent, the amount of expanded fly ash is 20 to 30 parts, exemplarily 22, 24, 26 or 28 parts, but not limited thereto. Preferably, the amount of expanded fly ash is 25 to 30 parts.
[0073] Specifically, the amount of lime used is 10 to 20 parts, exemplarily 11 parts, 14 parts or 17 parts, but not limited thereto. Preferably, the amount of lime used is 10 to 15 parts.
[0074] Specifically, the slag is S95 grade slag or S105 grade slag, but not limited thereto. Preferably, it is S95 grade slag. The amount of slag is 20 parts to 50 parts, and exemplarily, it is 24 parts, 28 parts, 32 parts, 36 parts, 40 parts or 44 parts, but not limited thereto. Preferably, it is 30 parts to 45 parts.
[0075] Specifically, the cement can be sulphoaluminate cement or silicate cement, preferably silicate cement. After using the expanded fly ash of the present invention, a higher initial strength is provided, so the requirement can be met by using conventional silicate cement. Specifically, the silicate cement is PO42.5 grade cement or PO52.5 grade cement, but is not limited thereto. Preferably, the cement is PO42.5 grade cement.
[0076] Specifically, the amount of cement is 20 to 30 parts, exemplarily 22, 24, 26 or 28 parts, but not limited thereto, preferably 20 to 25 parts.
[0077] Preferably, in one embodiment of the present invention, the soft soil solidifying agent further comprises 2 to 5 parts of a conditioning agent. The conditioning agent is selected from polyacrylamide and / or chitosan, and the conditioning agent can promote electrostatic neutralization of floccules in high-water content soft soil, destroy the floccules structure, make water more easily released, and then absorbed by the expanded fly ash. Preferably, the conditioning agent is selected from chitosan.
[0078] Correspondingly, the present invention also discloses a method for preparing the above-mentioned soft soil solidifying agent, which comprises:
[0079] S21: mixing lime, slag and cement uniformly to obtain a mixture;
[0080] S22: providing / preparing expanded fly ash;
[0081] S23: Pack the mixture and expanded fly ash separately to obtain.
[0082] Among them, steps S21 and S22 are not performed in any particular order, and those skilled in the art may first perform step S21 / S22 and then perform another step, or may perform both steps simultaneously.
[0083] Correspondingly, the present invention also discloses a method for using the soft soil solidifying agent, which comprises:
[0084] S31: mixing expanded fly ash with the shallow surface soft soil to be solidified;
[0085] Among them, on-site solidification machinery (such as concrete pump trucks, excavators, excavators with mixing heads, excavators with distributors, etc.) can be used to mix the expanded fly ash with the shallow surface soft soil to be solidified. The weight ratio of the expanded fly ash to the shallow surface soft soil to be solidified is 1: (30~50).
[0086] S32: mixing a mixture of lime, slag and cement with the shallow surface soft soil to be solidified;
[0087] The mixture is firstly slurried by adding water, the water content of the slurry is maintained at 50wt%~60wt%, and then the slurry is mixed with the soft soil layer through an in-situ solidification machine. The weight ratio of the mixture to the shallow surface soft soil to be solidified is 1: (25~30).
[0088] The present invention is described below with specific embodiments:
[0089] The soft soil used in the following embodiments has an initial moisture content of 65.8 wt% to 85.4 wt% and an organic matter content of about 4.3 wt% to 7.6 wt%.
[0090] Example 1
[0091] This embodiment provides a soft soil curing agent, and its formula is as follows:
[0092] 10 parts of lime, 50 parts of S95 grade slag, 20 parts of PO42.5 grade cement, and 20 parts of expanded fly ash.
[0093] Wherein, the preparation method of expanded fly ash is:
[0094] (1) The fly ash obtained by burning anthracite has a total SiO2 and Al2O3 content of 69.5wt%, a CaO content of 3.2wt%, and a loss on ignition of 1.4wt% at 1000℃.
[0095] (2) Mix acrylic acid with a neutralization degree of 65%, acrylamide, propylene glycol triglycidyl ether, and water in a weight ratio of 1:0.5:0.003:4, add fly ash in a weight ratio of fly ash to acrylic acid of 12:1, and mix well;
[0096] (3) Add ammonium persulfate as an initiator at 0.02 wt% of the weight of acrylic acid, react at 80°C for 15 h, filter, dry, crush, and sieve to obtain the material between 120 mesh and 200 mesh, which is expanded fly ash.
[0097] The preparation method of the soft soil curing agent in this embodiment is:
[0098] (i) mixing lime, slag and cement uniformly to obtain a mixture;
[0099] (ii) preparing expanded fly ash;
[0100] (iii) The mixture and fly ash are packaged separately to obtain the product.
[0101] Example 2
[0102] This embodiment provides a soft soil curing agent, and its formula is as follows:
[0103] 20 parts of lime, 20 parts of S95 grade slag, 30 parts of PO42.5 grade cement, and 30 parts of expanded fly ash.
[0104] Wherein, the preparation method of expanded fly ash and soft soil solidifying agent is the same as that in Example 1.
[0105] Example 3
[0106] This embodiment provides a soft soil curing agent, and its formula is as follows:
[0107] 13 parts of lime, 35 parts of S95 grade slag, 28 parts of PO42.5 grade cement, and 24 parts of expanded fly ash.
[0108] Wherein, the preparation method of expanded fly ash and soft soil solidifying agent is the same as that in Example 1.
[0109] Example 4
[0110] This embodiment provides a soft soil curing agent, and its formula is as follows:
[0111] 13 parts of lime, 35 parts of S95 grade slag, 24 parts of PO42.5 grade cement, and 28 parts of expanded fly ash.
[0112] Wherein, the preparation method of expanded fly ash is:
[0113] (1) The fly ash obtained by burning anthracite has a total SiO2 and Al2O3 content of 69.5wt%, a CaO content of 3.2wt%, and a loss on ignition of 1.4wt% at 1000℃.
[0114] (2) mixing fly ash with water to obtain a first slurry with a concentration of 25 wt%, stirring the mixture thoroughly, standing the mixture for stratification, and removing floating beads on the surface;
[0115] (3) flotation of the first slurry using diesel as a collector and 2-octanol as a foaming agent, filtering and drying the first slurry after flotation to obtain a first intermediate;
[0116] The weight ratio of diesel to fly ash is 0.6:1000, the weight ratio of octanol to fly ash is 0.5:1000, the flotation time is 5 min, and the aeration volume is 0.4 m 3 / (m 2 ·min).
[0117] (4) treating the first intermediate with a 25 g / L NaOH aqueous solution at 60° C. for 0.6 h to obtain a second intermediate; wherein the ratio of the first intermediate to the NaOH aqueous solution is 20 g:100 mL;
[0118] (5) mixing acrylic acid with a neutralization degree of 65%, acrylamide, propylene glycol triglycidyl ether, and water in a weight ratio of 1.7:0.6:0.002:4.5, adding the second intermediate in a weight ratio of the second intermediate to acrylic acid of 14:1, and mixing well to obtain a third intermediate;
[0119] (6) Add 1-hydroxycyclohexyl phenyl ketone as an initiator at a rate of 0.02 wt% of the weight of acrylic acid, react at 80°C for 15 h, filter, dry, crush, sieve, and take the material between 120 mesh and 200 mesh, which is expanded fly ash.
[0120] The preparation method of the soft soil solidifying agent in this embodiment is the same as that in Embodiment 1.
[0121] Example 5
[0122] This embodiment provides a soft soil curing agent, and its formula is as follows:
[0123] 13 parts of lime, 35 parts of S95 grade slag, 22 parts of PO42.5 grade cement, 28 parts of expanded fly ash, and 2 parts of chitosan.
[0124] Among them, the preparation method of expanded fly ash and soft soil solidifying agent is the same as that in Example 4.
[0125] Comparative Example 1
[0126] This comparative example provides a soft soil solidifying agent, and its formula is as follows:
[0127] 10 parts of lime, 50 parts of S95 grade slag, 20 parts of PO42.5 grade cement, and 20 parts of fly ash.
[0128] The fly ash is obtained by burning anthracite, and its total content of SiO2 and Al2O3 is 69.5wt%, its CaO content is 3.2wt%, and its ignition loss at 1000°C is 1.4wt%.
[0129] The preparation method of the soft soil curing agent in this comparative example is:
[0130] Mix all components evenly and package.
[0131] Comparative Example 2
[0132] This comparative example provides a soft soil solidifying agent, and its formula is as follows:
[0133] 10 parts of lime, 50 parts of S95 grade slag, 20 parts of 42.5R grade sulphoaluminate cement, and 20 parts of fly ash.
[0134] The fly ash is obtained by burning anthracite, and its total content of SiO2 and Al2O3 is 69.5wt%, its CaO content is 3.2wt%, and its ignition loss at 1000°C is 1.4wt%.
[0135] Test Example 1
[0136] Take soft soil samples and the soft soil curing agents in Examples 1 to 5, first mix the expanded fly ash and the soft soil in a ratio of 1:40, then mix the lime, slag and cement to make a slurry with a moisture content of 55wt%, then mix the mixture and the soft soil in a weight ratio of 1:25, and mold them into a cubic test mold of 70.7mm×70.7mm×70.7mm. After curing for 3d, 5d and 28d, the unconfined compressive strength (see "Cement Soil Mix Design Code" JGJ / T 233-2011) and permeability coefficient ("Highway Geotechnical Test Code" JTG 3430-2020) are tested respectively.
[0137] Comparative test example 1
[0138] The soft soil curing agent in Comparative Example 1 and Comparative Example 2 was subjected to a curing test, and the specific method is as follows:
[0139] Take the soft soil sample and the soft soil curing agent in Comparative Example 1 to Comparative Example 2, add water to make a slurry with a water content of 55wt%, and then mix the soft soil curing agent and the soft soil in a weight ratio of 1:25, and mold them into a cubic test mold of 70.7mm×70.7mm×70.7mm. After curing for 3d, 5d, and 28d, the unconfined compressive strength (see "Cement-Soil Mix Design Code" JGJ / T 233-2011) and permeability coefficient ("Highway Geotechnical Test Code" JTG 3430-2020) are tested respectively.
[0140] The specific test results are as follows:
[0141]
[0142] As can be seen from the above table, compared with the soft soil curing agent based on ordinary Portland cement (PO42.5), the soft soil curing agent of the present invention has higher strength in both the early and late stages of curing. Further, by controlling the preparation method of expanded fly ash, the early curing effect of the soft soil curing agent of the present invention can reach or even exceed the soft soil curing agent based on sulphoaluminate cement (Comparative Example 2), and in the late stage of curing, the soft soil curing agent of the present invention is more stable, while the soft soil curing agent based on sulphoaluminate cement has relatively low strength.
[0143] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.
Claims
1. A soft soil solidifying agent, characterized in that: The composition comprises the following components in parts by weight: 10~20 parts of lime, 20~50 parts of slag, 20~30 parts of cement, 20~30 parts of expanded fly ash; Wherein, the preparation method of the expanded fly ash comprises the following steps: (1) Sorting the fly ash to remove floating beads and carbon particles in the fly ash to obtain a first intermediate; (2) treating the first intermediate with an alkali solution having a concentration of 10 g / L to 30 g / L for 0.2 h to 0.5 h to obtain a second intermediate; (3) uniformly mixing acrylic acid, acrylamide, glycerol triglycidyl ether and water in a weight ratio of (1-2):(0.5-1.5):(0.001-0.005):(2-5), adding the second intermediate, and mixing thoroughly to obtain a third intermediate; wherein the weight ratio of the second intermediate to acrylic acid is (5-15):1, and the degree of neutralization of the acrylic acid is 60%-80%; (4) adding an initiator to the third intermediate and reacting at 60° C. to 90° C. for 10 h to 20 h to obtain a fourth intermediate; (5) Drying the fourth intermediate and crushing it to a size below 100 meshes to obtain expanded fly ash.
2. The soft soil solidifying agent according to claim 1, characterized in that: Step (1) includes: (1.1) Mix fly ash and water to obtain a first slurry with a concentration of 20wt% to 40wt%, and remove the floating beads on the surface after standing; (1.2) Using diesel as a collector and octanol as a frother, the first pulp is floated, and the first pulp after flotation is filtered and dried to obtain a first intermediate; The weight ratio of the diesel to the fly ash is (0.3-1.5):1000, the weight ratio of the octanol to the fly ash is (0.4-1.5):1000, the flotation time is 3-5 min, and the aeration volume is 0.1 m 3 / (m 2 ·min)~0.5m 3 / (m 2 ·min).
3. The soft soil solidifying agent according to claim 1, characterized in that: In step (2), the alkali solution is a NaOH aqueous solution or a KOH aqueous solution, and the temperature thereof is 50°C to 80°C; The ratio of the alkali solution to the first intermediate is 100 mL: (20-30) g.
4. The soft soil solidifying agent according to claim 1, characterized in that: The initiator is selected from one or more of azobisisobutylimidazoline hydrochloride, 1-hydroxycyclohexylphenyl ketone, ammonium persulfate, and potassium persulfate.
5. The soft soil solidifying agent according to claim 1, characterized in that: In step (2), the alkali solution is a NaOH aqueous solution, and the temperature thereof is 50°C to 70°C; and / or In step (3), acrylic acid, acrylamide, propylene glycol triglycidyl ether and water are uniformly mixed in a weight ratio of (1.5-2): (0.5-1): (0.001-0.003): (4-5), and the second intermediate is added and mixed thoroughly to obtain a third intermediate; wherein the weight ratio of the second intermediate to acrylic acid is (10-15): 1, and the degree of neutralization of the acrylic acid is 60%-70%; and / or In step (4), the initiator is 1-hydroxycyclohexyl phenyl ketone, the reaction temperature is 70° C. to 80° C., and the reaction time is 10 h to 15 h.
6. The soft soil solidifying agent according to any one of claims 1 to 5, characterized in that It also includes 2 to 5 parts of conditioner; The conditioning agent is polyacrylamide and / or chitosan.
7. The soft soil solidifying agent according to claim 1, characterized in that: The slag is S95 grade slag powder or S105 grade slag powder; and / or The cement is PO42.5 grade cement or PO52.5 grade cement.
8. A method for preparing a soft soil solidifying agent, for preparing the soft soil solidifying agent according to any one of claims 1 to 5 and 7, characterized in that: include: Mixing lime, slag and cement uniformly to obtain a mixture; Providing / preparing expanded fly ash; The mixture and the expanded fly ash are packaged separately to obtain the product.
9. A method for using the soft soil solidifying agent according to any one of claims 1 to 5 and 7, characterized in that: include: Mixing expanded fly ash with the shallow surface soft soil to be solidified; The mixture obtained by mixing lime, slag and cement is added into the shallow surface soft soil to be solidified which has been mixed with expanded fly ash, and mixed.
Citation Information
Patent Citations
High-performance concrete dry mixture and use method thereof
CN109678413A
Soft soil curing agent
CN111943625A